2005
DOI: 10.1300/j083v46n01_03
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Experience of Moving a Loved One to a Long-Term Care Facility

Abstract: This project was designed to develop an understanding of family members' experiences of moving a loved one to a long-term care facility and to identify ways in which facilities might help ease this process. Twenty-one semi-structured interviews were conducted with family members who had recently moved a relative into one of three long-term care facilities in Southern Ontario, Canada. Several factors appeared to contribute to the overall experience of the move to long-term care and either served to impede or fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 45 publications
2
33
0
1
Order By: Relevance
“…'Ambivalence' also bridges different lines of previous research referred to in the text: one line focusing primarily on enduring ties and value consensus (e.g. Dellasega & Nolan, 1997;Flynn Reuss, Dupuis & Whitfield, 2005;Strang, 22 Koop, Dupuis-Blanchard, Nordstrom, et al, 2006), the other primarily on caregiver stress and conflicts (e.g. Chenier, 1997;Coehlo, Hooker & Bowman, 2007;Dellasega & Mastrian, 1995).…”
Section: Concluding Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…'Ambivalence' also bridges different lines of previous research referred to in the text: one line focusing primarily on enduring ties and value consensus (e.g. Dellasega & Nolan, 1997;Flynn Reuss, Dupuis & Whitfield, 2005;Strang, 22 Koop, Dupuis-Blanchard, Nordstrom, et al, 2006), the other primarily on caregiver stress and conflicts (e.g. Chenier, 1997;Coehlo, Hooker & Bowman, 2007;Dellasega & Mastrian, 1995).…”
Section: Concluding Discussionmentioning
confidence: 76%
“…As concerns family members, in several countries they are increasingly expected to play a more significant role both in the initial decision to seek help and subsequently in selecting a residential home (Davies & Nolan, 2003;Dellasega & Mastrian, 1995;McAuley, Travis & Safewright, 1997). Correspondingly, previous research within the area has largely been focused on the family members' uncertainty and their need to validate the decisions they make (Dellasega & Mastrian, 1995;Penrod & Dellasega, 1998;Ryan & Scullion, 2000), as well as on the lack of available information and support mechanisms (Flynn Reuss, et al, 2005;Kellett, 1999). Sandberg, Lundh & Nolan (2002) have studied the roles of adult children who support a caregiving parent in the placement process of an often life-long partner.…”
Section: Family Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from the Care Quality Commission (2010) indicated that almost half of users of adult inpatient services were "definitely" not involved in decisions about their care to the extent they wanted. Carers may consider that the responsibility associated with looking after an older adult in their own home is unmanageable (Penrod and Dellasega, 2001) and describe a sense of relief on care home admission of a relative (Reuss, 2005). Further, the potential for older adults to return to the community following admission to a care home is enhanced if a family member is supportive of the decision to return home (Arling et al, 2010).…”
Section: Choosing the Pathmentioning
confidence: 99%
“…10 Studies have also examined perspectives of residents who transitioned to different levels of care (ALF or SNF) within a CCRC, 19 stress experienced by family caregivers associated with the transfer of a relative to a long-term care facility, 20 and risk factors associated with the ALF to SNF transition. 21 Seven qualitative research studies have examined transitions from ALFs.…”
Section: Introductionmentioning
confidence: 99%